Student Involvement in Construction Supervision and Its Implications for Professional Competence Formation in Architectural Education: A Comparative Case Study - Pamungkas, Luhur Sapto; Tisnawati, Endah; Fadillah, Rizky Gilang; Saputra, Rio Fian; Ciptaning Puspitasari, Endah (International Journal of Science, Technology & Management, 2026)
Internship programs in undergraduate architectural education are often positioned as assistive activities without a clear conceptual framework regarding their contribution to professional competence formation. This study aims to formulate a conceptual model of student involvement in construction supervision and to explain the mechanism through which field experience is transformed into professional competence. A qualitative comparative case study approach was employed in two different project contexts: a medium-scale private project and a public government facility project. Data were collected through analysis of internship reports, daily logbooks, time-stamped visual documentation, and students’ reflective notes. The analysis was conducted using intra-case analysis, pattern matching, and cross-case explanation building. The findings reveal a consistent causal pattern in which student involvement in supervision stages enhances technical exposure and structured reflective documentation, which subsequently stimulates professional reflection and the internalization of both technical and professional competencies. The study produces a refined conceptual model that clarifies the mediating mechanism between field experience and professional identity formation in architectural education. Curricularly, the findings recommend integrating structured supervision modules and reflective documentation instruments into internship courses to ensure measurable and systematic learning outcomes.